La iniciativa Yasuní ITT como opción alternativa al protocolo de Kyoto para la comercialización de bonos de carbono - Altamirano Erazo, Cecilia Katerine (2013)
Nowadays, concerns about the environment have increased becoming in a global interest. As a result, nations around the world have established legislation in order to control the danger of nature. As a consequence, The United Nations Convention on weather change and Kyoto Protocol were created. Both regulation look for mitigate the negative effects of weather changing by creating sinks and the clean technology mechanisms. Consequently, both methods are helping countries to have less pollution by lessen Co2 emissions in order to stop worldwide destruction. Ecuador is leading a project called Socio Bosque which will help people to protect Ecuadorian forests and badlands. Therefore, government has to pay forests and badlands’ owners so that they can well preserved those ones avoiding indiscriminate felling